2013
DOI: 10.1371/journal.pone.0067086
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anesthetics on Immune Functions in a Rat Model of Vagus Nerve Stimulation

Abstract: Vagus nerve stimulation (VNS) has been successfully performed in animals for the treatment of different experimental models of inflammation. The anti-inflammatory effect of VNS involves the release of acetylcholine by vagus nerve efferent fibers inhibiting pro-inflammatory cytokines (e.g. TNF-α) produced by macrophages. Moreover, it has recently been demonstrated that splenic lymphocytic populations may also be involved. As anesthetics can modulate the inflammatory response, the current study evaluated the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
0
11
0
2
Order By: Relevance
“…A significant exception can be attributed to Martelli and colleagues (Martelli et al, 2014a) who demonstrated, in conscious rats, that the splanchnic anti-inflammatory pathway has a powerful and sustained inhibitory influence on inflammatory processes. It is well known that anesthetics interfere particularly with the neural mechanisms modulating the immune system (Picq et al, 2013). For instance, several studies showed that ketamine and isoflurane exhibit potent anti-inflammatory properties (Flondor et al, 2008; Hofstetter et al, 2005; Qin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A significant exception can be attributed to Martelli and colleagues (Martelli et al, 2014a) who demonstrated, in conscious rats, that the splanchnic anti-inflammatory pathway has a powerful and sustained inhibitory influence on inflammatory processes. It is well known that anesthetics interfere particularly with the neural mechanisms modulating the immune system (Picq et al, 2013). For instance, several studies showed that ketamine and isoflurane exhibit potent anti-inflammatory properties (Flondor et al, 2008; Hofstetter et al, 2005; Qin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In general, volatile anesthetics induced a decrease in proliferation of lymphocytes or an increase in lymphocyte apoptosis. 9,119121 …”
Section: Adaptive Immunitymentioning
confidence: 99%
“…Moreover, anesthetic drugs interfere with the neuronal activation and they also showed anti-inflammatory properties. As consequence, these properties may not represent a real effect of nerve stimulation in a systemic inflammatory condition [51]. Another limitation of using the electrical vagus nerve stimulation in sepsis therapies involves the high rates of splenic lymphocytes apoptosis.…”
Section: The Inflammatory Reflexmentioning
confidence: 99%